Street Art and the Struggle for Public Space - Muttaqin, M. Zaenul (Street Art & Urban Creativity, 2023)
The film entitled "Coretan Seni Dibalik Vandalisme" is an Indonesian-language documentary film that offers street art from a broader perspective, beyond the values ​​of legality and democracy. The views of artists, observers, and academics are important to capture the reorientation of street art which has been commonly called vandalism.